THE INFLUENCE OF LEARNING INTEREST ON THE WRITING SKILLS OF PROCEDURE TEXTS FOR GRADE XI - Nani Mulyani; Euis Eti Rohaeti (IKIP Siliwangi, 2021)
AbstractThis study aims to prove whether there is an influence of learning interest on the ability to write procedural texts. The hypothesis tested is that there is an influence of interest in learning Bahasa Indonesia on the ability to write procedural texts. This study uses a quantitative description method because the research data is in the form of numbers, analyzed using statistics and describes the relationship between variables. The number of samples was 62 students of class XI SMK PP Negeri Sumedang. The instruments used in this research are test and non-test. The test instrument is in the form of a procedure text writing skill test result. Meanwhile, the non-test instrument was in the form of a questionnaire containing 20 indicators of interest including attention, enthusiasm, great desire, and interest in learning bahasa Indonesia. The results of the correlation analysis is 0.689, it indicates that there is a strong relationship between the interest in learning Bahasa Indonesia and the ability to write procedural texts. The regression value (r) square is 0.839, it indicates the influence of the independent variable on the dependent variable. Test the significance or significance of the regression coefficient obtained sig. 0.000 < 0.05 and tcount = 17.665. There is a significant effect of interest in learning bahasa Indonesia on the ability to write procedural texts.